Top-down and bottom-up regulation in a high nutrient-high herbivory coastal ecosystem - Martinetto, P. (2011)
In this study, carried out in San Antonio Bay (Northern Argentinean Patagonia), we aimed to understand the relative importance of bottom-up and top-down controls on macroalgal blooms in a macrotidal system with high nutrient supply and high consumer abundance. Our results show that nutrients, pH, and O 2 concentrations were higher during low tide. A field experiment showed that the biomass accumulation rate of Ulva lactuca ranged from 6 to 12% d -1 and was reduced by herbivory by 60%. The biomass accumulation rate did not differ in thalli with different initial internal nutrient pools. There was a negative relationship between the percentage of algae consumed and the N content in algal tissues, suggesting compensatory feeding by herbivores. Herbivory reduced the biomass accumulation rate of U. lactuca when PO 4 3- or no nutrients were added, but not when NO 3 - was added. In the absence of herbivory, the addition of nutrients did not increase U. lactuca biomass accumulation rate. These results suggest that nutrients remain high enough for adequate time intervals to be assimilated by macroalgae and support blooms. Large water exchange during tidal changes, however, can diminish the potential negative effects of macroalgal accumulation (oxygen depletion, high ammonium concentrations) on herbivores such that herbivores can have a large impact on macroalgae. © Inter-Research 2011.